Improved space vector modulation with reduced switching vectors for multi-phase matrix converter - Ahammed, S. K. Moin (2016)
Multi-phase converter inherits numerous advantages, namely superior fault tolerance, lower per-leg power rating and higher degree of freedom in control. With these advantages, this thesis proposes an improved space vector modulation (SVM) technique to enhance the ac-to-ac power conversion capability of the multi-phase matrix converter. The work is set to achieve two objectives. First is to improve the SVM of a three-to-seven phase single end matrix converter by reducing number of space vector combinations. Second is to use the active vector of the SVM to eliminate the common-mode voltage due to the heterogeneous switching combination of a dual three-to-five phase matrix converter. In the first part, the proposed technique utilizes only 129 out of 2,187 possible active space vectors. With the reduction, the SVM switching sequence is greatly simplified and the execution time is shortened. Despite this, no significant degradation in the output and the input waveform quality is observed from the MATLAB/Simulink simulation and the hardware prototype. The results show that the output voltage can reach up to 76.93% of the input voltage, which is the maximum physical limit of a three-to-seven phase matrix converter. In addition, the total harmonics distortion (THD) for the output voltage is measured to be below 5% over the operating frequency range of 0.1 Hz to 300 Hz. For the second part, the common-mode voltage elimination is based on the cancellation of the resultant vectors (that causes the common-mode to be formed), using a specially derived active vectors of the dual matrix converter. The elimination strategy is coupled with the ability to control the input power factor to unity. The proposed concept is verified by the MATLAB/Simulink simulation and is validated using a 5 kW three-to-five phase matrix converter prototype. The SVM switching algorithm itself is implemented on a dSPACE-1006 digital signal processor platform. The results prove that the common-mode voltage is successfully eliminated from the five-phase induction motor winding. Furthermore, the output phase voltage is boosted up to 150% of the input voltage in linear modulation range.